A Qualitative Inquiry Into the Sources of Resilience Found Among Maximum Security Correctional Officers - Gist, Jon T.A. (Criminal justice policy review, 2023)
Resilient individuals are better able to cope with trauma, and overcome life’s adversities. Correctional officers are routinely exposed to workplace stressors that can be psychologically harmful. For these essential workers, resilience, therefore, offers a way to counteract the aversive conditions of their employment. In light of its importance in promoting mental wellness, studies have explored antecedents of resilience, yet few of which were conducted among correctional officers. To address this literature void, open-ended questionnaire data were collected from maximum-security corrections officers (N = 193) working in a southeastern state to understand the factors they believe most crucial in developing resilience. Respondents identified seven key themes associated with resilience, including co-worker support, establishing purpose in life, individual characteristics, self-care, life balance, prayer/meditation, and finally, maintaining positive attitudes. Results are discussed in light of interventions targeted at improving correctional officer mental health.